The Advisor: Counsel, Concealment, and Machiavelli's Voice. (1st October 2017) - Goodman, Rob
Abstract : Machiavelli's political works should be read not only as attempts to shape princely behavior, but as demonstrations of a model of advisory behavior. They are a performance of advice-giving, of the dispassionate, scientistic – but also quietly radical – behavior Machiavelli expects of those tasked with speaking to power. This model's central feature is concealment of argument and rhetorical intent, a feature inherited from classical rhetoric but put to newly expansive use. This article turns from Machiavelli's appropriation of the "mirror" literature's concept of flattery, a kind of counter-ideal of advisory behavior, to his development of the classical rhetoric of self-effacement. It argues that he puts this rhetorical tradition to newly expansive use – not as a proto-scientist of politics but as a dynamic political actor in his own right – inventing ostensibly neutral dilemmas, classifications, and frames to guide the ruler-reader, as if voluntarily, toward some of his most distinctive conclusions.